Bound to the group and blinded by the leader: ideological leader–follower dynamics in a trust economic game. Issue 9 (25th September 2019) - Gjoneska, Biljana; Liuzza, Marco Tullio; Porciello, Giuseppina; Caprara, Gian Vittorio; Aglioti, Salvatore M.
Abstract : Understanding the dynamics of trustworthiness in ideological contexts could influence human societies, affect electoral campaigns and ultimately impact democracy. We tested trust behaviour towards political leaders in a sample of 121 opposing/supporting voters assigned as trustors in an iterative trust game (TG). In two experiments, a famous Italian conservative leader (i.e. Silvio Berlusconi) or a famous non-politician were used as trustees in a predefined un/trustworthy TG, while trustors believed that mathematical algorithms reproduced trustee's real behaviour. Results revealed that depending on the group, voters either relied on the situation and adjusted to the behaviour of the out-group leader (in our case left-wing voters), or on their disposition for group-loyalty with respect for authority, thus failing to adjust to the behaviour of the in-group leader (in our case right-wing voters). Our findings suggest that: (i) complex voter–leader relations in politics are reflected in the simple trustor–trustee financial interactions from behavioural economics, and (ii) being bound to one's group and one's leader may affect the trust economic decisions of the followers.